Information Needs for Climate Change Adaptation among Farmers of Uttrakhand, India - Anjali Chunera and Amardeep (Indian Journal of Extension Education, 2018)
The study attempts to determine the information needs for climate change adaptation and preferenceof farmersaboutcommunication media and methods in the hilly region of Uttarakhand. Using the multistage samplingprocedure, a total of 300 men and women farmers were selected through Probability Proportionate to Sizemethod from the villages. Pretested interview schedule was used for collecting the information. The findingsshow that the major areas of information needs of farmers on adaptation strategies to climate change werewaterharvesting schemes,crop management strategies, drought/flood tolerant crop varieties, control of animaldiseases, climate change tolerant livestock breeds, quality of feed/fodder, sources for credit, climate-smartagriculture practices and technology andinsurances.It was also found that farm and home visit was the mostpreferred method to receive information. Extensive efforts along with the application of emerging informationcommunication technologies for the information-oriented farming community are required in order to impartinformation to farmers related to climate change adaptations